Atomatisasi Penentuan Jenis Kerusakan Motor Matic Merk NMAX Yamaha Menggunakan Metode Forward Chaining - Willy Eka Septian; Yuhandri Yunus (SEULANGA SYSTEM PUBLISHER, 2021)
Easy access to motorcycle has now made almost all people own motorcycle. However, there are many obstacles in motorcycle maintenance, especially N-Max motorcycle. The lack of knowledge about engine failure has resulted in many owners choosing the workshop to be the destination for detecting motorcycle damage. Then the research was carried out by applying the Forward Chaining method to detect damage to the N-Max motorcycle. The result of this research is that the owner of the Yamaha N-Max motorcycle can find out the damage to the motorcycle early and get the solution suggested by the system. This study resulted in 86.7% of the success rate of this system.